Pembelajaran Daring selama Pandemi COVID-19 dari Perspektif Mahasiswa Calon Guru Agama Katolik: Tantangan dan Peluang - Emmeria Tarihoran (Jurnal Penelitian Pendidikan Agama Katolik, 2022)
This study aims to determine the challenges and opportunities in the implementation of online learning at STP-IPI Malang during the Corona Virus 19 (Covid-19) pandemic from a student perspective. This research is a descriptive qualitative research with research subjects are students of the Catholic Religious Education Study Program (PKK). The data was obtained through a survey with an open questionnaire which was circulated through the Google form. Data analysis was carried out using Miles and Huberman's interactive analysis technique with the stages of data reduction, data presentation and inference. The data reduction stage is carried out by grouping all the data obtained according to the specified category. In addition, the presentation of data based on categories regulated according to regulations then eliminates things that are not appropriate. The next stage provides meaning and conclusions from the processed data as a result. The results of the study show that online learning opportunities offer opportunities to learn how to use technology with the available functions, helping students to be more creative and gain the ability to shape learning using the tools available in the technology devices used. However, in reality the tendency to be lazy, interact less with peers, lack discipline, get bored easily, and lack focus in learning is a challenge that dominates students. It is strongly felt that the application of self-building learning which is the hallmark of the PPAK Study Program cannot be implemented effectively and maximally.